Facile conversion of chromane-6-triflate to chromane-6-alanines under Palladium conditions - Miller, Daniel K. (2013)
Conversion of chromane-6-triflate 5 to chromane-6-dehydroalanine 9 or 10 via its Bpin-derivative 6 followed by Suzuki coupling with protected dehydroalanine bromides 7 or 8 were reported (86%). Alternatively, a palladium-catalyzed stannation of 5 with Bu(6)Sn(2) afforded the tributyltin derivative 11, and iodination (12) followed by coupling with 13 gave chromane-6-alanine 15 (75%). Either approach constitutes a conversion from chromane-6-triflate to the corresponding protected chromane-6-alanine or its dehydro analog.